A likely runaway star cluster in the outer disc of the Large Magellanic Cloud - Piatti, Andres Eduardo (2018)
We present results from photometric and spectroscopic data obtained with SOAR and Gemini observatory facilities in the field of a recently discovered star cluster. The cluster, projected towards the Eastern side of the outer disc of the Large Magellanic Cloud (LMC),was originally placed nearly 10 kpc behind the LMC with an age and metallicity typical of the innermost LMC star cluster population.We assigned radial velocity (RV) memberships to stars observed spectroscopically, and derived the cluster age and distance from theoretical isochrone fitting to the cluster colour-magnitude diagram. The new object turned out to be a 0.9 Gyr old outer LMC disc cluster, which possibly reached the present position after being scattered from the innermost LMC regions where it might have been born. We arrived at this conclusion by examining the spatial distribution of LMC star clusters of similar age, by comparing the derived spectroscopic metallicity with that expected for an outside-in galaxy formation scenario, by considering the cluster internal dynamical stage as inferred from its derived structural parameters and by estimating the circular velocity of a disc that rotates with the corresponding star cluster radial velocity at the cluster's deprojected distance, which resulted to be nearly 60 per cent higher than that of most of the outer LMC disc clusters.